2015
DOI: 10.1080/15433714.2013.849218
|View full text |Cite
|
Sign up to set email alerts
|

Intentions to Engage in Evidence-Based Practice among Undergraduate Social Work Students: Preliminary Findings from Romania

Abstract: Knowledge and familiarity of evidence-based practice (EBP) is a key competence to social workers entering the workforce. The literature review revealed no studies on Romanian graduates that have measured the beliefs, attitudes, knowledge, and behaviors students have about EBP in the final semester of their bachelor's of social work (BSW) degree program. A sample of 89 students drawn from one public school in Romania completed the instrument. The questionnaire included measures of familiarity, attitudes, feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…Previous research demonstrates that most social workers are positive toward EBP, although a minority report that they are critical or skeptical toward the concept (Bergmark & Lundström, 2011;Heiwe et al, 2013;Iovu, 2015;Iovu et al, 2015;James et al, 2019;Van Der Zwet et al, 2016;Wilson & Douglas, 2007). Similar results have been found among social work students (Iovu, 2015;Parrish & Rubin, 2012).…”
Section: Previous Research On Social Workers' Attitudes Toward Ebpsupporting
confidence: 68%
See 1 more Smart Citation
“…Previous research demonstrates that most social workers are positive toward EBP, although a minority report that they are critical or skeptical toward the concept (Bergmark & Lundström, 2011;Heiwe et al, 2013;Iovu, 2015;Iovu et al, 2015;James et al, 2019;Van Der Zwet et al, 2016;Wilson & Douglas, 2007). Similar results have been found among social work students (Iovu, 2015;Parrish & Rubin, 2012).…”
Section: Previous Research On Social Workers' Attitudes Toward Ebpsupporting
confidence: 68%
“…Previous research demonstrates that most social workers are positive toward EBP, although a minority report that they are critical or skeptical toward the concept (Bergmark & Lundström, 2011;Heiwe et al, 2013;Iovu, 2015;Iovu et al, 2015;James et al, 2019;Van Der Zwet et al, 2016;Wilson & Douglas, 2007). Similar results have been found among social work students (Iovu, 2015;Parrish & Rubin, 2012). Although a majority of social workers demonstrate positive attitudes toward EBP, unfamiliarity and confusion surrounding the concept still persist (Avby et al, 2014;Bergmark & Lundström, 2011;Ekeland et al, 2018;Grady et al, 2018;James et al, 2019;Wilson & Douglas, 2007).…”
Section: Previous Research On Social Workers' Attitudes Toward Ebpsupporting
confidence: 59%
“…Two of the three papers (Brown et al, ; Iovu, ) reported significant Pearson's Product Moment bivariate correlations between independent and dependent variables of EBP future use and intention to use EBP, prior to model development, whereas the third study (Forsman et al., ) reported Pearson's correlations between the intention to use research evidence as a dependent variable and the outcome variable of research use 1‐year postgraduation. Correlations as reported are presented in Table S4.…”
Section: Resultsmentioning
confidence: 99%
“…After a systematic search and selection process, only three papers were included in the review (Brown, Kim, Stichler, & Fields, ; Forsman, Wallin, Gustavsson, & Rudman, ; Iovu, ). Details of the search and selection process are reported in the PRISMA flowchart (Moher, Liberati, Tetzlaff, Altman, & The PRISMA Group, ), as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation